An assessment of the extent of environmental mercury contamination in the vicinity of Thor Chemicals, Cato Ridge, Kwa Zulu-Natal, South Africa and the subsequent health risk communities consuming fish in the area are exposed to - Oosthuizen, Jacques De Villiers (Department of Public Health and Family Medicine, 2018)
Environmental mercury pollution of the Valley of a Thousand Hills area of KwaZulu-Natal, South Africa, in particular the river system below the Thor Chemicals mercury recycling plant, has been a topic of heated debate for a number of years. Thor Chemicals was established as a mercury recycling plant in the mid-1980' s and it processed mercury waste imported from various countries. A number of factory workers were subsequently exposed to high levels of mercury vapour causing the death of a worker. Upon investigation it was found that in addition to the occupational exposures of workers, mercury waste had been discharged into the river systems of the Valley of a Thousand Hills. During the 1998 South African Parliamentary session, questions were raised regarding the lack of adequate monitoring and research directed at quantifying human health risks in the region. A number of Government departments were accused of apathy and incompetence in adequately addressing the issue. Fish forms an important part of the diet of the local community living in the Valley of a Thousand Hills. Children, in particular, are frequently observed fishing in the rivers, thus placing these individuals at risk should the fish be contaminated with mercury. The aims of this study were: to determine the extent of environmental mercury pollution of the river system downstream from the Thor Chemicals plant, and to quantify the human health risk associated with fish consumption in the region. Samples of streambed sediment, algae, cattle hair, fish and human hair, were obtained from the study area as well as from a control area upstream from the Thor Chemicals plant. These were analysed to determine the concentration of mercury in each sample. Mercury levels in the study group were compared to mercury levels in the control areas.